2011
DOI: 10.5251/ajsms.2011.2.2.208.216
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of factors affecting the technical efficiency of cocoa farmers in the Offinso district -Ashanti region, Ghana

Abstract: This paper analysed the factors that affect the technical efficiency of cocoa farmers in the Offinso district in Ghana. The study also analysed the basic determinants of technical efficiency, as well as the socio-economic variables that affect their performances. Primary data was collected through the administration of questionnaires. Stata statistical tool was used to estimate the stochastic production frontier function and the inefficiency determinants based on socioeconomic variables of individual farmers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 21 publications
5
11
0
Order By: Relevance
“…This indicates that the more educated the farmers were, the more technically efficient they were. This conforms to a priori expectation and is in line with previous findings (Amos, 2007;Kyei et al, 2011). Table 2 also shows that the coefficient of membership of cooperative was significant at 5% and negatively related to technical inefficiency (hence, positively influenced the technical efficiency) of the uninsured farm operators.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This indicates that the more educated the farmers were, the more technically efficient they were. This conforms to a priori expectation and is in line with previous findings (Amos, 2007;Kyei et al, 2011). Table 2 also shows that the coefficient of membership of cooperative was significant at 5% and negatively related to technical inefficiency (hence, positively influenced the technical efficiency) of the uninsured farm operators.…”
Section: Resultssupporting
confidence: 91%
“…While many studies have focused on analysing technical efficiency of cocoa farmers in general (Amos, 2007;Nyemeck Binam et al, 2008;Kyei et al, 2011), none of them has attempted to make a comparative analysis of technical efficiency of insured and uninsured cocoa farm activities in particular. This is a research gap which this study was designed to fill.…”
Section: Introductionmentioning
confidence: 99%
“…The results is an indication that majority of the farmers were ageing. The result also corroborates the findings of Kyei et al (2011) and Idowu et al (2007) which revealed that 65% and 68% of cocoa farmers in Ashanti Region in Ghana and southwest Nigeria respectively were over 50 years of age. None of the farmers was less than 20 years of age while only 4.1% were between the age of 21 to 30 years, This also indicates that less youth were taking part in cocoa farming.…”
Section: Resultssupporting
confidence: 90%
“…In particular, the increased use of pesticides makes it possible to control insects and brown rot which generally attack cocoa. This result is similar to that found in Ghana by Kyei, Gordon and Ankoh [21]. These researchers had shown that the increase in pesticide quantities in cocoa fields in the Offinso district of Ghana had a positive effect on cocoa production.…”
Section: Discussionsupporting
confidence: 79%